Variety of Bio-Hydrocarbon precursors for the synthesis of carbon nanotubes - Azmina, M.S.; Bakar, S.A.; Salina, M.; Azira, A.A.; Dalila, A.R.; Asli, N.A.; Rosly, J.; Nor, Roslan Md; Rusop, M. (2012)
In this work, we have synthesized carbon nanotubes (CNT) using different bio-hydrocarbon precursors namely palm, olive, coconut, corn and sesame oils. Prior to the synthesis process, thermogravimetric analysis (TGA) characterization was performed on the carbon precursors to facilitate the optimization procedures of CNT and reach maximum yield and higher quality CNT. The CNT arrays were deposited on a silicon substrate by thermal catalytic decomposition of the precursor using 5.33 wt ferrocene. The synthesis was carried out at 750 Â°C for 60 min under argon ambient. The samples were characterized using field emission scanning electron microscopy, micro-Raman spectroscopy and TGA analysis. The difference in oil density resulted in different quality and tube diameter of CNT produced. Among all, the CNT synthesized from coconut oil can be considered as the best bio-hydrocarbon precursor for higher quality (ID/IG ~0.62) and good purity (81.95 ) CNT.